2016
DOI: 10.3390/ijms17122035
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of Blood Serum and Plasma Pre-Analytics for Metabolomics Cohort Studies

Abstract: The recent thriving development of biobanks and associated high-throughput phenotyping studies requires the elaboration of large-scale approaches for monitoring biological sample quality and compliance with standard protocols. We present a metabolomic investigation of human blood samples that delineates pitfalls and guidelines for the collection, storage and handling procedures for serum and plasma. A series of eight pre-processing technical parameters is systematically investigated along variable ranges commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 41 publications
11
67
0
Order By: Relevance
“…demonstrated that a high number of metabolites are significantly altered as a consequence of prolonged processing times at different temperatures, including signaling metabolites, lipids, carbohydrates, and amino acids. However, the most important changes can be associated with energy‐related metabolites (i.e., increased lactate, decreased glucose, and pyruvate), which could be attributable to the anaerobic metabolism of erythrocytes . Thus, as a general recommendation, blood processing times should be reduced to the minimum (preferably no longer than 2 h) and samples should be kept cool in the meantime.…”
Section: Sample Characteristics and Preanalytical Processingmentioning
confidence: 99%
“…demonstrated that a high number of metabolites are significantly altered as a consequence of prolonged processing times at different temperatures, including signaling metabolites, lipids, carbohydrates, and amino acids. However, the most important changes can be associated with energy‐related metabolites (i.e., increased lactate, decreased glucose, and pyruvate), which could be attributable to the anaerobic metabolism of erythrocytes . Thus, as a general recommendation, blood processing times should be reduced to the minimum (preferably no longer than 2 h) and samples should be kept cool in the meantime.…”
Section: Sample Characteristics and Preanalytical Processingmentioning
confidence: 99%
“…Hence, the sample handling is a relevant pre‐analytical factor significantly affecting the stability of the metabolome . Recently many studies examined several sample handling conditions relating to sample pre‐processing, storage and the variability of metabolite levels over time . That knowledge is required to estimate the reproducibility of metabolite measurements.…”
Section: Markers Of Sample Qualitymentioning
confidence: 99%
“…This presents a great potential for their use in critical care medicine for understanding the relationships between the factors of microorganisms and the course of the pathological process that is key to improving the disease outcomes. [1] Metabolomics promotes the development of "personalized" medicine based on the application of patientspecific profiles, incorporating genetic and genomic data as well as clinical and environmental factors, to assess individual risks and to improve diagnostics and the target treatment. [2,3] GNS of humans and animals has a wide range of neurogenic and non-neurogenic functions, many of which are still little known.…”
Section: Introductionmentioning
confidence: 99%